Stem-End Rind Breakdown of Citrus Fruit - Mark A. Ritenour; Huating Dou (EDIS)
Sporadic reports of stem-end rind breakdown (SERB) on fresh citrus fruit occur each season in Florida. SERB is most severe on oranges and Temples, but it may also occur on tangelos and grapefruit. Although there is still much that needs to be learned about the development and prevention of SERB, there are some principles that can be applied to help reduce SERB development in fresh fruit packed in Florida. This document is HS936, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2003.